Editors’ Remarks Vol.10(1) - Adhikari, H.C. (JODEM: Journal of Language and Literature, 2019)
It is a matter of great joy for the members of Department of English Mahendra Multiple Campus Dharan that is has been again successful in bringing out 12th issue (vol. 10, No. 1) of JODEM, Journal of Department of English MMC, Dharan. Ever since its first publication, it has come a long way and been successful in enhancing the quality and standard of the journal because of the incessant efforts made by its members. It is hoped that the Department will certainly continue the publication of the journal in the years ahead. The present issue contains twelve peer reviewed articles. These articles have been contributed not only by the Department members of MMC but also by members who come from other campuses. The articles are based on feminism, gender study, cultural study, ecocriticism, study of language / linguistics and the study of diaspora. The genres these writers have made use of are fiction, non-fiction, poetry and linguistics.